The Asessment of Liberal Arts Students’ Behavioral Intention and Use Behavior of Mobile Video Apps in Chongqing, China - Wei, Ran (Scholar: Human Sciences, 2023)
Purpose: Generation Z people are reported to be main users of Internet and mobile video applications. Thus, this study aims to assess the influencing factors of behavioral intention and use behavior towards mobile video apps, using a case of Gen Z students in liberal arts in Chongqing, China. Research design, data and methodology: The researchers used quantitative research methods and nonprobability sampling techniques including purposive, quota and convenience samplings for the data collection. 500 college students in liberal arts program who have been using mobile video apps in Chongqing, China, were invited to participate in the study. Item Objective Congruence (IOC) Index and Cronbach’s Alpha reliability were approved before the data collection process. Afterwards, structural equation model (SEM) and confirmatory factor analysis (CFA) were used for the data analysis and results. Results: Perceived ease of use, social influence, habit and facilitating conditions have a significant affect behavioral intention. Furthermore, behavioral intention significantly affects use behavior. On the other hand, perceived usefulness has no significant effect on behavioral intention. Conclusions: This study validates factors impacting Gen Z’s adoption on mobile video editing applications which mobile developers are recommended to emphasize this major group of user’s use behavior for the better development of the apps.